Mechanistic and structural basis for activation of cardiac myosin force production by omecamtiv mecarbil - Vicente J. Planelles-Herrero (Nature Portfolio, 2017)
Omecamtiv mecarbil (OM) is a cardiac myosin activator that is currently in clinical trials for heart failure treatment. Here, the authors give insights into its mode of action and present the crystal structure of OM bound to bovine cardiac myosin, which shows that OM stabilizes the pre-powerstroke state of myosin.